2016
DOI: 10.1128/jcm.02128-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Matrix-Assisted Laser Desorption Ionization−Time of Flight Mass Spectrometry for Identification of Mycobacterium species, Nocardia species, and Other Aerobic Actinomycetes

Abstract: The value of matrix-assisted laser desorption ionization؊time of flight mass spectrometry (MALDI-TOF MS) for the identification of bacteria and yeasts is well documented in the literature. Its utility for the identification of mycobacteria and Nocardia spp. has also been reported in a limited scope. In this work, we report the specificity of MALDI-TOF MS for the identification of 162 Mycobacterium species and subspecies, 53 Nocardia species, and 13 genera (totaling 43 species) of other aerobic actinomycetes us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 14 publications
2
75
1
Order By: Relevance
“…As it allows pathogen-specific culture and protein extraction protocols (34,35), we first optimized our in-house mycobacterial cell disruption and protein extraction protocol for MALDI-TOF MS analysis. Upon comparison of various described protocols using M. tuberculosis H37Rv cells (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), we found that in our hands, bead beating in the presence of 1.2 ml of 70% ethanol gave the best output in terms of peak intensity and identification scores (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it allows pathogen-specific culture and protein extraction protocols (34,35), we first optimized our in-house mycobacterial cell disruption and protein extraction protocol for MALDI-TOF MS analysis. Upon comparison of various described protocols using M. tuberculosis H37Rv cells (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), we found that in our hands, bead beating in the presence of 1.2 ml of 70% ethanol gave the best output in terms of peak intensity and identification scores (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike most bacteria, mycobacteria require prior inactivation and disruption of the mycolic acid-rich cell wall, both for biosafety reasons and to liberate the cellular protein content. Numerous suitable procedures have been proposed, combining heat-killing, ethanol, sonication, and/or silica-based bead beating preceding the regular formic acid/acetonitrile extraction (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The reported success rates vary between 55% and 98% correct species-level identifications, but the large variety in strain collections, culture conditions, extraction protocols, hardware, and databases hinder data comparison between publications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of mycobacteria has not reached an optimal level of routine testing yet and published studies showed discrepant performances, depending on spectrometer, extraction method, algorithm, library, media, and biomass used for the assays (15)(16)(17)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In this study, we compared two distinct databases of Vitek-MS, the Saramis v4.12 open database and the new IVD v3.0 closed database.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially evaluated with mycobacterial intact cells (9)(10)(11)(12), but several investigators worked on improving inactivation and protein extraction (13)(14)(15)(16)(17)(18)(19)(20). Most published studies assessed the performance of MALDI-TOF BioTyper (Bruker Daltonics, Bremen, Germany) (15,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Few of them evaluated Vitek MS (bioMérieux, Marcy l'Etoile, France) (16,17,20,24,25,32).…”
mentioning
confidence: 99%